Translanguaging as a Dynamic Strategy for Heritage Language Transmission - Sviatlana Karpava; Natalia Ringblom; Anastassia Zabrodskaja (Languages)
This study explores translanguaging as a flexible and adaptive strategy for heritage language transmission within multilingual families residing in Cyprus, Estonia, and Sweden. Using a qualitative approach, the research examines family language policies, parental beliefs, and the linguistic practices of bilingual and multilingual families, where one parent speaks Russian. The findings reveal how translanguaging supports bilingual development by fostering linguistic adaptability, bridging heritage and societal languages, and accommodating diverse sociolinguistic contexts. Parents in each country implement unique strategies, influenced by local linguistic landscapes, educational systems, and resource availability. In Cyprus, some families strictly adhered to structured methods like the One Parent–One Language strategy, while others adopted a more integrative multilingual approach, seamlessly translanguaging between Russian, Greek, and English in their daily interactions. Estonian and Swedish families display pragmatic adaptations, emphasizing translanguaging’s role in promoting the emotional well-being and linguistic identity of family members. However, certain challenges persist, including societal language dominance, literacy and educational resource scarcity, and the potential overuse of translanguaging in formal communication. By comparing these contexts, the study underscores the need for flexible yet deliberate family language policies, institutional support, and community resources to sustain bilingualism in bilingual and multilingual families. This research contributes to understanding translanguaging’s implications for intergenerational language transmission in minority and immigrant settings, offering insights for educators, linguists, and policymakers on fostering linguistic diversity and equity in globalized societies.